2019
DOI: 10.1186/s13065-019-0605-8
|View full text |Cite
|
Sign up to set email alerts
|

Oligosaccharide-based quality evaluation of Atractylodis rhizome and a strategy for simplifying its quality control

Abstract: Background Atractylodis rhizoma, is the dried rhizomes of Atractylodes lancea (Thunb.) DC. or A. chinensis (DC.) Koidz. Both of two are pharmacologically and economically important, while with differences in efficacy. Therefore, an authentication system is vital for evaluation the quality and discrimination adulteration of Atractylodis rhizoma. Fructooligosaccharides (FOS), which are regarded as functional ingredients in Atractylodis rhizoma, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
1
6
0
2
Order By: Relevance
“…Lin et al (2010) reported RSD of 2.59-11.43% for intra-day and 7.12-11.9% for inter-day precision in LC-MS inulin quantification. Similar results were reported in the study of Zhuang et al (2019) where they obtained intra-day precision of 0.29-4.43% and inter-day precision of 5.74-10.91% for three different concentrations (n = 6), and accuracy of 83.16-99.6% (n = 3) in HPLC-ELSD analysis of inulin-type fructooligosaccharides.…”
Section: Repeatability and Reproducibilitysupporting
confidence: 89%
“…Lin et al (2010) reported RSD of 2.59-11.43% for intra-day and 7.12-11.9% for inter-day precision in LC-MS inulin quantification. Similar results were reported in the study of Zhuang et al (2019) where they obtained intra-day precision of 0.29-4.43% and inter-day precision of 5.74-10.91% for three different concentrations (n = 6), and accuracy of 83.16-99.6% (n = 3) in HPLC-ELSD analysis of inulin-type fructooligosaccharides.…”
Section: Repeatability and Reproducibilitysupporting
confidence: 89%
“…Множество гликозидных связей и трудности экстракции для получения ОС с ненарушенной структурой препятствуют развитию технологий химического синтеза аналитических стандартов высокомолекулярных ОС. В поисках выхода из сложившейся ситуации изучаются возможности извлечения и очистки стандартов ОС в аналитических лабораториях с помощью твердофазной экстракции, высокоэффективной жидкостной хроматографии (HPLC) или их комбинации [37]. Так, например, Li et al [38] извлекли и очистили стандарты КОС (степень полимеризации 2-6; чистота > 99%) с использованием твердофазной экстракции с последующей хроматографией гидрофильного взаимодействия (HILIC).…”
Section: особенности контроля олигосахаридовunclassified
“…Данные Zhuang et al [37] подтверждают более высокую чувствительность HPLC-ELSD по сравнению с HPLC-RID, а также стабильность исходного уровня благодаря совместимости с градиентным элюированием и независимости от температуры. Последующие работы исследователей позволили увеличить чувствительность метода.…”
Section: методы количественной оценки олигосахаридовunclassified
“…The branch chain consists of →3, 5)-Araf-(1→, →5)-Araf-(1→, and Araf-(1→. A series of oligo-saccharides DP 3-15 were separated from A. lancea and identified as FOS, which consisted of linear β-(2, 1)-linked fructofuranosyl units mostly carry a terminal single α-(1–2)-linked α-glucopyranosyl unit ( Zhuang et al, 2019 ). The ACPS was extracted via ultrasonic method in enzymolysis A. lancea.…”
Section: Phytochemistrymentioning
confidence: 99%